Functional gastrointestinal disorders in children from low socio‐economic status and Helicobacter pylori infection. (14th July 2017) - Jaime, F.; Villagrán, A.; Hernández, C.; Ortiz, M.; Serrano, C.; Harris, P. R.
Abstract: Background: Most studies on functional gastrointestinal disorders (FGIDs) in children are based on data from the northern hemisphere. Scientific reports are arising in South American population, but little is still known about children from low socio‐economic status (SES), where Helicobacter pylori infection is endemic. Our objective was to evaluate the prevalence of FGIDs in school children from low SES and its relationship with H. pylori infection. Methods: Children from 3 public schools of low SES from Santiago de Chile were included. Students completed the Rome III Questionnaire and a survey about other symptoms. Also, the 13 C urea breath test determined the presence of H. pylori infection. Results: Five hundred six children were included, where 48% were male, with a median age of 15.7 years (range 7.1–19.6). Forty‐two percent had some FGID, aerophagia and functional constipation being the most frequent. Females (adjusted OR 1.5, 95% CI [1.1, 2.2]), those children with parents within the lowest level of education (adjusted OR 1.6, 95% CI: 1.1–2.4), and family history of gastric cancer (adjusted OR 1.9, 95% CI: 1.2–3.1) were related to FGIDs. The prevalence of H. pylori infection was 55.9% (95% CI [50.7, 60.9]). In multivariable analysis, the presence of abdominal pain (OR 1.55, 95% CI [1.02, 2.36]), but not FGIDs, was related to H. pylori infection. Conclusions: FGIDs are common in low SES students. A low educational level of the household head, family history of gastric cancer. and being female are related to the development of FGIDs. In this study, no relationship between the presence of H. pylori and FGIDs was found.